GE_GERICHTE A/2383/2022 vom 22. Mai 2023 - GE Cour de justice (2023)
IMPÔT SUR LES SUCCESSIONS ET LES DONATIONS;TESTAMENT;ACTION EN NULLITÉ(DROIT DES SUCCESSIONS);TRANSACTION(ACCORD) | LDS.6A.al1.leta; LDS.20